생산단계 참나물의 Carbendazim 잔류특성에 따른 노출평가 및 농약 잔류허용기준 개선 - 장희라; Hee-ra Chang; 곽혜민; Hye-min Gwak (Hanguk hwangyeong nonghak hoeji, 2022)
BACKGROUND: The residue dissipation pattern of pesticides for agricultural products during the pre-harvest period after the final application is important to prevent the maximum residue limit (MRL) violations in domestic and export markets. The MRL violations of carbendazim are observed more often in chamnamul by pesticide residue management surveys by the Ministry of Food and Drug Safety. The residue level at the pre-harvest interval (PHI) and the residue dissipation constant from the critical good agricultural practice (cGAP) trials could be estimated to meet the MRL and pose a health risk to consumers. METHODS AND RESULTS: Chamnamuls were harvested at 0, 1, 3, 5, 7, 10, and 14 days after application of carbendazim in accordance with critical GAP. The residue analysis in chamnanul was performed by HPLC-DAD with the C18 column. The limit of quantitation of carbendazim was 0.04 mg/kg, and the recoveries were 74.4 - 95.8% at the two spiked levels (LOQ and 10LOQ) of carbendazim. The dissipation rates in chamnamul were calculated from the residues at the sampling days by statistical method at a 95% confidence level. The biological half-lives of residual carbendazim in the field trials 1 and 2 were 4.9 and 4.4 days, respectively. CONCLUSION(S): In this dissipation study, the residue concentrations at the recommended PHI were higher than the established MRL in Korea. Therefore, the MRL is proposed based on the residue data sets from the trials conducted at the same cGAP and the dietary exposure assessment.